2023
DOI: 10.3390/antibiotics12071190
|View full text |Cite
|
Sign up to set email alerts
|

Native-Valve Aspergillus Endocarditis: Case Report and Literature Review

Abstract: Aspergillus endocarditis represents the second etiological cause of prosthetic endocarditis following Candida spp. On the other hand, native-valve endocarditis due to Aspergillus are anecdotally reported with increasing numbers in the last decade due to new diagnostic technologies such as polymerase chain reaction (PCR) on samples like valve tissue or entire blood. We performed a review of the literature presenting one case report observed at Pisa University Hospital. Seventy-four case reports have been includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA ( 27 ). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA ( 28 , 29 ). The synergistic effects between different antifungal agents may provide a wider range of antifungal activities.…”
Section: Discussionmentioning
confidence: 99%
“…Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA ( 27 ). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA ( 28 , 29 ). The synergistic effects between different antifungal agents may provide a wider range of antifungal activities.…”
Section: Discussionmentioning
confidence: 99%
“…Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA (27). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA (28,29). The synergistic effects between different antifungal agents may provide a wider range of antifungal activities.…”
Section: Discussionmentioning
confidence: 99%
“…Feys et al reported a case of disseminated aspergillosis involving CNS and lung, successfully treated by intracerebral liposomal AmB combined with intravenous ISA (27). Furthermore, there have been cases of fungal endocarditis successfully treated with dual antifungal therapy using liposomal AmB and ISA (28,29). The synergistic effects between different antifungal agents may provide a wider range of antifungal activities.…”
Section: Discussionmentioning
confidence: 99%